Invasive shigellosis in MSM. (September 2016) - Serafino Wani, Robert L; Filson, Sarah A; Chattaway, Marie A; Godbole, Gauri
Shigella flexneri is an emerging pathogen in men who have sex with men (MSM); recent outbreaks related to sexual practices have been noted in this population in the UK and other developed countries. While the majority of cases of shigellosis present with gastroenteritis, some vulnerable patients with underlying immunosuppression can develop complications like bacteraemia and may present atypically as an acute surgical emergency. This case report highlights such a case of S. flexneri bacteraemia in a man who had sex with men.